COVID-19 Pneumonia: The Great Ultrasonography Mimicker - Lacedonia, Donato; Quarato, Carla Maria Irene; Mirijello, Antonio; Trovato, Guglielmo M.; Del Colle, Anna; Rea, Gaetano; Scioscia, Giulia; Foschino Barbaro, Maria Pia; Sperandeo, Marco (Frontiers in Medicine, 2021)
The pandemic spread of the new Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has raised the necessity to identify an appropriate imaging method for early diagnosis of coronavirus disease 2019 (COVID-19). Chest Computed Tomography (CT) has been regarded as the mainstay of imaging evaluation for pulmonary involvement in the early phase of the pandemic. However, due to the poor specificity of the radiological pattern and the disruption of Radiology Centers functionality linked to an excessive demand for exams, the American College of Radiology (ACR) has advised against CT use for a screening purpose. Lung ultrasound (LUS) is a point-of care imaging tool that is fast available and easy to disinfect. These advantages have determined a “pandemic” increase of its use for early detection of COVID-19 pneumonia in Emergency Departments. However, LUS findings in COVID-19 patients are even less specific than those detectable on CT scan. The scope of this perspective article is to discuss about the great number of diseases and pathologic conditions that may mimic COVID-19 pneumonia on LUS examination.